History and structure of the LENS - Cerbai, Elisabetta; Schettino, Vincenzo (Il Colle di Galileo, 2022)
The article tells the story of the origins of the LENS as an open international facility for the performance of advanced research on lasers and their applications in physics, chemistry, biology and medicine. The laboratory’s current situation is described, with references to what has been achieved so far and indications of future prospects.